An observational study on the effect of hypercholesterolemia developed after living donor liver transplantation on cardiac event and graft failure - Jungchan Park (Nature Portfolio, 2021)
Abstract This study sought to evaluate the association between newly-developed significant hypercholesterolemia within one year following living donor liver transplantation (LDLT) and long term outcomes in light of cardiovascular events and graft failure. From October 2003 to July 2017, 877 LDLT recipients were stratified according to development of significant hypercholesterolemia within one year following LDLT. The primary outcome was occurrence of a major adverse cardiac event (MACE), defined as a composite of cardiac death, myocardial infarction, and coronary revascularization after LDLT. The incidence of graft failure, defined as all-cause death or retransplantation, was also compared. A total of 113 (12.9%) recipients developed significant hypercholesterolemia within one year. The differences in incidences of cardiac related events and graft related events began emerging significantly higher in the hypercholesterolemia group after 24 months and 60 months since the LDLT, respectively. After adjustment using the inverse probability of weighting, the hazard ratio (HR) for MACE was 2.77 (95% confidence interval (CI) 1.16–6.61; p = 0.02), while that for graft failure was 3.76 (95% CI 1.97–7.17, p < 0.001). A significant hypercholesterolemia after LDLT may be associated with cardiac and graft-related outcome; therefore, a further study and close monitoring of cholesterol level after LDLT is needed.